Pengelolaan Lingkungan Berbasis Kebijakan Publik di Kota Pekanbaru - Oka Suleman; Zulkarnaini Zulkarnaini (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Urban environmental management has become an important issue in modern times, particularly in Pekanbaru, a city experiencing rapid growth and high levels of urbanization. This study aims to analyze public policy-based environmental management in Pekanbaru, focusing on the effectiveness of policies implemented by the local government to preserve environmental sustainability. Using a qualitative approach, data were collected through interviews with government officials, environmental experts, and local residents, as well as a review of relevant policy documents. The findings indicate that although existing environmental management policies are relatively comprehensive, there are several challenges in their implementation, including a lack of public awareness, limited funding, and suboptimal coordination between sectors. Therefore, this study recommends improvements in inter-agency coordination, increased public participation, and regular evaluations of policies to enhance the effectiveness and sustainability of environmental management in Pekanbaru. In this way, public policy-based environmental management is expected to contribute to the creation of a green, clean, and livable city.